Production and Phytochemical Variation of Kaempferia rotunda Rhizomes in Relation to Soil Nutrient Conditions on Madura Island - Sholehah, Diana Nurus; Risqiyah, Risqiyah; Putri, Suci Aulia; Umam, Choirul; Fadlilaturrahmah, Fadlilaturrahmah; Suryawati, Sinar (Tropical Biopharmaca Research Center, IPB University, 2026)
Kaempferia rotunda L. is a traditional medicinal plant in Madura. This study aimed to evaluate the production and phytochemical variation of K. rotunda rhizomes from Madura Island and to determine the soil chemical factors associated with these traits. Plant materials and soil samples were collected from ex situ cultivation areas in Bangkalan, Sampang, Pamekasan, and Sumenep. Rhizome production, simplicia yield, extract yield, total phenolics, total tannins, total steroids, and soil nutrient contents were analyzed. The results showed substantial variation among accessions in both production and phytochemical contents. Primary rhizome weight was positively correlated with the number of secondary rhizomes, whereas secondary rhizome simplicia yield was positively correlated with total rhizome simplicia yield. Soil nutrients showed low-to-moderate correlations with production traits but strong correlations with phytochemical contents. Suitable accession selection combined with balanced macro- and micronutrient availability may improve rhizome yield and quality.